Kształt polityki spójnośći Unii Europejskiej w Polsce w latach 2007–2013 - Willa, Rafał (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
Poland has been a full member of the European Union for five years already. One of the results of this membership is the opportunity to obtain co-financing for domestic investments and activities, provided via structural funds. Both Polish society and potential beneficiaries (e.g. businesses, provinces, institutions, NGOs) have enormous expectations in this respect. However, these expectations are not based on genuine awareness of the objectives of the EU’s financial instruments, the principles of their planning, implementation, or their actual impact. Since the significance of EU cohesion policy among other EU policies continues to rise, it is necessary to examine its present shape and compare it with the former budget programming period. This will allow one to envisage the direction this policy is taking, as it is shaped by the subsequent reforms. Additionally, this knowledge may be crucial at present, when the funds provided by the EU’s’ financial perspective 2007–2013 are being spent, and it may also be useful in the near future, during the negotiations on the shape of cohesion policy after 2013, also including the subject of Poland’s maintaining the status of one of the largest beneficiaries of the Union’s financial support.